Bioinspired Hairy Skin Electronics for Detecting the Direction and Incident Angle of Airflow - Chun, Sungwoo; Son, Wonkyeong; Choi, Changsoon; Min, Hyeongho; Kim, Jiwon; Lee, Heon Joon; Kim, Dongjin; Kim, Changhwan; Koh, Je Sung; Pang, Changhyun (ACS Applied Materials and Interfaces, 2019)
The human skin has inspired multimodal detection using smart devices or systems in fields including biomedical engineering, robotics, and artificial intelligence. Hairs of a high aspect ratio (AR) connected to follicles, in particular, detect subtle structural displacements by airflow or ultralight touch above the skin. Here, hairy skin electronics assembled with an array of graphene sensors (16 pixels) and artificial microhairs for multimodal detection of tactile stimuli and details of airflows (e.g., intensity, direction, and incident angle) are presented. Composed of percolation networks of graphene nanoplatelet sheets, the sensor array can simultaneously detect pressure, temperature, and vibration, all of which correspond to the sensing range of human tactile perceptions with ultrahigh response time (<0.5 ms, 2 kHz) for restoration. The device covered with microhairs (50 μm diameter and 300 μm height, AR = 6, hexagonal layout, and ∼4400/cm 2 ) exhibits mapping of electrical signals induced by noncontact airflow and identifying the direction, incident angle, and intensity of wind to the sensor. For potential applications, we implement the hairy electronics to a sailing robot and demonstrate changes in locomotion and speed by detecting the direction and intensity of airflow.
Keywords: Electrical signal; Flexible device; High aspect ratio; microhair; Multimodal detection; Percolation networks; Structural displacement; Tactile perception; Electronics; Graphite; Hair; Humans; Pressure; Robotics; Skin; Touch; biosensor; E-skin; flexible device; graphene; microhair